Morphogenesis of stockpiled Marandu, Piatã, Xaraés and Paiaguás brachiariagrass cultivars - M.E.R. Santos; I.C. Ferreira; B.H.R. Carvalho; G.O. Rocha; G.S. Borges; D.M. Oliveira (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2021)
ABSTRACT The objective this study was to identify differences in the morphogenic patterns of four Urochloa brizantha cultivars (marandu, piatã, xaraés and paiaguás grasses) during the stockpiling period. A completely randomized design was used, with three replications, in experimental plots of 9m². The evaluations took place over 2 years. The grasses were stockpiled for 92 (Year 1) and 95 (Year 2) days. The leaf appearance rate of paiaguás grass was higher, compared to other grasses. In Year 1, the stem elongation rate of xaraés grass was higher than other grasses. At the end of stockpiling period of Year 1, the tiller population density (TPD) was higher in the paiaguás grass, intermediate in the xaraés and marandu grasses and lower in the piatã grass. At the end of the stockpiling period in Year 2, TPD was higher in the paiaguás grass canopy, intermediate in the marandu and piatã grasses canopies, and lower in the xaraés grass canopy. Paiaguás grass has greater leaf growth during the stockpiling period and is therefore suitable for use under stockpiled grazing. Xaraés grass has high stem elongation during the stockpiling period, which is why its use under stockpiled grazing must be accompanied by adjustments in pasture management.